How Perceived Usefulness, Ease of Use, and Quality Affect E-Wallet Intention in Gen Y and Z: A TAM Perspective - Haedar, Shafiq; Marsasi, Endy Gunanto (SENTRALISASI, 2025)
This study aims to evaluate the effect of perceived ease of use, perceived usefulness, and quality on intention to use e-wallets among generations Y and Z. The method used was quantitative, and questionnaires were distributed to 236 respondents in several cities in Java. The study used Structural Equation Modeling with IBM SPSS 29 software and AMOS Graphic 26 to test the proposed hypothesis. The results showed that both subjective norms significantly positively influence perceived ease of use, increasing perceived usefulness. Quality also contributes positively to perceived usefulness and perceived trust. However, the relationship between perceived trust and intention to use was not significantly proven. These findings provide important insights for e-wallet service providers to develop interface design and service quality to encourage wider adoption among young users. The Technology Acceptance Model theory serves as the foundation for this study, which analyses the factors that influence technology acceptance by contributing to developing more effective marketing strategies and product designs for increasing e-wallet usage among the younger generation.